The impact of sonication cell size and distance on near field temperature in Magnetic Resonance Guide High Intensity Focused Ultrasound - Yot, Ng Chiak (2018)
Objective: The purpose of this study is to determine correlation between sonication cell size and sonication distance with mean peak temperature changes within the near field and using MR thermometry during MR-HIFU. The other purpose of this study is to formulate a prediction of therapeutic response in between sonication cell size and sonication distance with mean peak temperature changes within the near field. Methodology: Sonication distance and sonication cell size was controlled respectively, Total of 125 sonication was performed. For each 5 repetitions of sonication for a preset parameter, a mean peak temperature is measured. Univariate (Pearson correlation) and multivariate (linear regression) was performed to determine correlation and determine predictions of therapeutic response is done. The level of significance is calculated and the P value of less than 0.05 is statistically significant. Results: There is statistically significant correlation between sonication cell size and mean peak temperature changes in the near field, with p value less than 0.05. However, no statistically significant correlation between sonication distance and mean peak temperature changes, with p value of 0.08. Regression analysis indicates that sonication cell size significantly predicted mean temperature changes in the near field. [R2 = .654, F (1, 23) = 46.307, p < .001] Predicted mean temperature changes in the near field is equal to 37.1 + 0.32 (sonication cell size) in millimeters when the mean temperature is measured in Celsius. Mean temperature changes in the near field increased 0.32 with each millimeter of sonication cell size. Conclusion: There is statistically significant correlation between sonication cell size and mean peak temperature changes in the near field however no statistically significant correlation between sonication distance and mean peak temperature changes.